Effect of different salinity levels on the prosome lenght of Pseudodiaptomus annandalie (Copepoda Calanoida). - Prudente, Pia Marie Lee P
The study aimed to determine the effect of different salinity levels on the prosome length of P. annandalie. P. annandalie samples were collected from brackish water ponds and cultured in fifteen 25L tanks for ten days. Sampling was done each day for ten days and twenty individuals were measured for their prosome length. Two-Way Analysis of variance (ANOVA) at 5 level of significance showed no effect of salinity on the prosome length. Significant results, however, were found on the effect of culture days on the prosome length. On the last days, of culture, an increase of prosome length in all salinity levels was observed. Significant results were obtained on the effect of salinity and days of culture on the prosome width P. annandalie. An increase in the prosome width values was observed on the last days of culture.